Improvement of Cycle Capability of Fe-Substituted Li2S-Based Positive Electrode Materials by Doping with Lithium Iodide. Issue 3 (27th December 2018) - Takeuchi, Tomonari; Kageyama, Hiroyuki; Nakanishi, Koji; Kiuchi, Hisao; Katayama, Misaki; Inada, Yasuhiro; Ohta, Toshiaki; Fukunaga, Toshiharu; Sakaebe, Hikari; Kobayashi, Hironori; Matsubara, Eiichiro
Abstract : For an attempt to improve the cycle capability of the Li8 FeS5 cells, we have prepared LiI-doped Li8 FeS5 composite positive electrode materials. The obtained Li8 FeS5 · x LiI sample cells showed the improved cycle capability, though the initial capacity value decreased with proportional to the mass of LiI. The improved cycle performance was attributable to the suppressed resistance rise of the cells, due probably to the suppression of high-resistive surface precipitates formed by the reaction between the active material and the electrolyte. The dopant LiI would stabilize the local structure against Li extraction/insertion reactions, as well as suppress the reaction with the electrolyte, leading to the improved cycle performance.